Bruxelles, le nouveau Berlin ? - Boris Grésillon; Tatiana Debroux (Belgeo)
Endowed with a dense artistic landscape, the city of Brussels seems to be in the midst of an intense cultural renewal. While traditional institutions suffer, like the federal museums and the royal opera house, new art spaces are created such as the contemporary art centre Wiels. Moreover, the opening of a large museum of modern and contemporary art in a former industrial site in 2020 is intended to position Brussels among the European cultural metropolises, alongside Paris and Berlin. In its cultural trajectory, the Belgian capital shows some interesting similarities with the German capital. Assuming that the current Brussels cultural landscape shows resemblance with the “Berlin model” of the 1990s, this paper argues that a fruitful comparison is worth between two of the most discussed European metropolises. The Berlin prism offers to put Brussels and its cultural scenes in perspective.